Restoration of patterned vision with an engineered photoactivatable G protein-coupled receptor. Issue 1 (December 2017) - Berry, Michael; Holt, Amy; Levitz, Joshua; Broichhagen, Johannes; Gaub, Benjamin; Visel, Meike; Stanley, Cherise; Aghi, Krishan; Kim, Yang Joon; Cao, Kevin; Kramer, Richard H.; Trauner, Dirk; et al.
Abstract Retinitis pigmentosa results in blindness due to degeneration of photoreceptors, but spares other retinal cells, leading to the hope that expression of light-activated signaling proteins in the surviving cells could restore vision. We used a retinal G protein-coupled receptor, mGluR2, which we chemically engineered to respond to light. In retinal ganglion cells (RGCs) of blindrd1 mice, photoswitch-charged mGluR2 ("SNAG-mGluR2") evoked robust OFF responses to light, but not in wild-type retinas, revealing selectivity for RGCs that have lost photoreceptor input. SNAG-mGluR2 enabled animals to discriminate parallel from perpendicular lines and parallel lines at varying spacing. Simultaneous viral delivery of the inhibitory SNAG-mGluR2 and excitatory light-activated ionotropic glutamate receptor LiGluR yielded a distribution of expression ratios, restoration of ON, OFF and ON-OFF light responses and improved visual acuity. Thus, SNAG-mGluR2 restores patterned vision and combinatorial light response diversity provides a new logic for enhanced-acuity retinal prosthetics. To restore sight after retinal degeneration, one approach is to express light-sensitive proteins in remaining cells. Here the authors combine a light-sensitive engineered G protein-coupled receptor and ion channels to restore ON and OFF responses as well as superior visual pattern discrimination.